Originally Posted by

**Phire** 2y^2 + x - 16y + 26 = 0

- x = 2y^2 - 16y + 26 (Moved x to the other side)

- x = 2(y^2 - 8y + 13) (Factored out 2)

x = - 2(y^2 - 8y + 13) (Divide sides by -1)

x + 26 = - 2(y^2 - 8y) (Move 13 to the left side, but first multiply it by -2, resulting in -26, therefore add 26 to each side)

x + 26 **+** 32 = - 2(y^2 - 8y + 16) (Complete the square on the right side, add 16 to both sides, but it has to be multiplied by -2 before I bring it to the left side, which results in -32, therefore add 32 to the left side.

x + 58 = - 2(y-4)^2

x = - 2(y-4)^2 - 58

This answer is wrong, where did I go wrong?